Studi Pengelolaan Keuangan Desa dari Perspektif Permendagri Nomor 113 Tahun 2014 - Purwa Astawa, I Wayan; Budiasih, I Gusti Ayu Nyoman (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 2 (2019)DO - 10.24843/JIAB.2019.v14.i02.p08, 2019)
Tabanan Regency, the perspective of Permendagri 113 Year 2014. This research is descriptive qualitative, research data obtained through in-depth interviews, observation and documentation studies, which were then analyzed by Case Study method. The results of the study interpreted the management of Peken Dauh village in the perspective of Permendagri 113 of 2014. showed that the implementation of the Village Expenditure Budget had been carried out by the Dauh Peken Village but was not fully in accordance with the provisions where there were still non-conformities in the technical planning, implementation and accountability of village financial administration. This discrepancy required the synergy of the district and sub-district governments in terms of assistance and supervision of village financial management.   Keywords: village finance, regulations, village finance providers.